Control interno del departamento de avalúos y catastros y su repercusión en los ingresos del gobierno autónomo descentralizado del Cantón El Empalme año 2011 - Guato Bermello, Lila Yessenia (2012)
The Government Decentralized Autonomous Municipality of the Canton the splice is a public institution for social, cultural and economic development, with legal personality and indefinite duration whose objective is to serve the people Empalmense. This research work includes the study and evaluation of internal control of the activities that are performed in the Department of appraisals and Cadastres Decentralized Autonomous Government of the Municipality of the Canton The Splice whose objective is to determine the proper functioning of the administrative area of the DepartmentThe Department of the same of which depend on the revenue streams to the municipality as it is a vital source of information on the taxes generated by several urban and rural sites. Therefore, this department is in the axis of the Municipal Administration since that of this depends on the filter of the timely information that serves as a support for the collection of revenue that are carried out in the treasury department, proceeds going to the annual budget for public works of the Canton. This investigative work is a tool for the officials of the department subject to assessment because in this we were able to determine the requirements of the program to strengthen and play activities based on appropriate procedures that will yield better results. For the realization of this work has been needed for a budget of about two hundred and fifty and six dollars intended for the good development of the present work.